2015
DOI: 10.1001/jamaophthalmol.2015.2721
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lateral Comitance After Asymmetric Horizontal Strabismus Surgery

Abstract: IMPORTANCE Asymmetric horizontal strabismus surgery is often performed to correct primary gaze alignment without considering the symptoms that may result from misalignment in the patient's side gaze. Surgical choices influence alignment in side gaze and may contribute to functional and social deficits. OBJECTIVE To identify the surgical procedures associated with changes of alignment in side gaze to help inform surgical planning for patients with horizontal strabismus. DESIGN, SETTING, AND PARTICIPANTS The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…Lateral incomitance can be large enough to influence surgical planning. 41 , 43 In a recent study, 63/155 patients (41%) undergoing surgery for intermittent exotropia had lateral incomitance of >5 prism-diopters. 44 For patients with sizeable incomitance in primary gaze, such as those identified in our study, one might consider performing slightly asymmetrical surgery to obtain optimal results.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral incomitance can be large enough to influence surgical planning. 41 , 43 In a recent study, 63/155 patients (41%) undergoing surgery for intermittent exotropia had lateral incomitance of >5 prism-diopters. 44 For patients with sizeable incomitance in primary gaze, such as those identified in our study, one might consider performing slightly asymmetrical surgery to obtain optimal results.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Graeber et al , 90% of patients having postoperative lateral incomitance had undergone asymmetrical surgery 32. While another study in children undergoing asymmetrical surgery, reported that 30% of cases with postoperative induced incomitance, had diplopia in side gazes, while 30% had concerns regarding their cosmetic appearance in side gazes even after 6 months 32 35. On the contrary, unilateral surgery reduced the preoperative lateral incomitance in half of the cases 32.…”
Section: Surgical Modalitiesmentioning
confidence: 97%
“…While another study in children undergoing asymmetrical surgery, reported that 30% of cases with postoperative induced incomitance, had diplopia in side gazes, while 30% had concerns regarding their cosmetic appearance in side gazes even after 6 months 32 35. On the contrary, unilateral surgery reduced the preoperative lateral incomitance in half of the cases 32. However, the evidence to show that unilateral surgery can induce lateral incomitance is scarce with only a couple of studies reporting the phenomenon, and more evidence is needed.…”
Section: Surgical Modalitiesmentioning
confidence: 98%
See 2 more Smart Citations